Fluoxetine Promotes Hippocampal Oligodendrocyte Maturation and Delays Learning and Memory Decline in APP/PS1 Mice - Chao, Feng-lei; Zhang, Yi; Zhang, Lei; Jiang, Lin; Zhou, Chun-ni; Tang, Jing; Liang, Xin; Fan, Jin-hua; Dou, Xiao-yun; Tang, Yong (Frontiers in Aging Neuroscience, 2021)
Oligodendrogenesis dysfunction impairs memory consolidation in adult mice, and an oligodendrocyte abnormality is an important change occurring in Alzheimer’s disease (AD). While fluoxetine (FLX) is known to delay memory decline in AD models, its effects on hippocampal oligodendrogenesis are unclear. Here, we subjected 8-month-old male amyloid precursor protein (APP)/presenilin 1 (PS1) mice to the FLX intervention for 2 months. Their exploratory behaviors and general activities in a novel environment, spatial learning and memory and working and reference memory were assessed using the open-field test, Morris water maze and Y maze. Furthermore, changes in hippocampal oligodendrogenesis were investigated using stereology, immunohistochemistry, immunofluorescence staining and Western blotting techniques. FLX delayed declines in the spatial learning and memory, as well as the working and reference memory of APP/PS1 mice. In addition, APP/PS1 mice exhibited immature hippocampal oligodendrogenesis, and FLX increased the numbers of 2‘3‘-cyclic nucleotide 3‘-phosphodiesterase (CNPase)+ and newborn CNPase+ oligodendrocytes in the hippocampi of APP/PS1 mice. Moreover, FLX increased the density of SRY-related HMG-box 10 protein (SOX10)+ cells and reduced the percentage of oligodendrocyte lineage cells displaying the senescence phenotype (CDKN2A/p16INK4a) in the hippocampus of APP/PS1 mice. Moreover, FLX had no effect on the serotonin (5-HT) 1A receptor (5-HT1AR) content or number of 5-HT1AR+ oligodendrocytes, but it reduced the content and activity of glycogen synthase kinase 3 (GSK3β) in the hippocampus of APP/PS1 transgenic mice. Taken together, FLX delays the senescence of oligodendrocyte lineage cells and promotes oligodendrocyte maturation in the hippocampus of APP/PS1 mice. FLX may regulate GSK3β through a mechanism other than 5-HT1AR and then inhibit the negative effect of GSK3β on oligodendrocyte maturation in the hippocampus of an AD mouse model.